Assessing Environmental Impacts of Groundwater Irrigation Using the Life Cycle Assessment Method: Application to a Tunisian Arid Region. (17th April 2018) - Pradeleix, Ludivine; Bouarfa, Sami; Bellon‐Maurel, Veronique; Roux, Philippe
Abstract: Groundwater irrigation is an opportunity to improve yield, but it also brings about a variety of environmental impacts that go beyond the most noticeable impact of water depletion. In this paper, a multi‐criteria environmental impact assessment based on life cycle analysis (LCA) is conducted at the regional level on the Kairouan Plain (Tunisia) where groundwater withdrawals for irrigation purposes are constantly increasing. At this regional level, we have addressed impacts of both groundwater pumping and cropping practices. The diversity of farming and cropping systems was also accounted for. Results highlight that the main processes contributing to the impacts on resources—when overlooking impacts on water depletion—are: energy used for groundwater pumping (23%), fertilization (30%), i.e. road transportation of manure (21%), ammonium nitrate manufacturing (9%), and also the manufacturing of irrigation pipes (13%). However, the specific impacts of freshwater depletion on natural resources are by far the most severe when accounted for in the method. Indeed, it is essential that these impacts on freshwater depletion be fully accounted for in this water‐scarce context, especially given the increasing water scarcity predicted by climatic models. Copyright © 2018 John Wiley & Sons, Ltd. Résumé: L'agriculture irriguée permet certes d'améliorer les rendements mais entraîne aussi de nombreux impacts environnementaux, au delà de l'épuisement de la ressource en eau. Les auteurs ont conduit une évaluation environnementale multi‐critère de type Analyse de Cycle de Vie (ACV) à l'échelle de la région de Kairouan en Tunisie où l'irrigation sur nappe est en constante augmentation. A cette échelle régionale, nous avons inclus tant les impacts dus au pompage et à l'irrigation que ceux dus aux pratiques agricoles, dont l'application de fertilisants et pesticides. La diversité des systèmes de production et de culture a aussi été prise en compte. Les résultats ont montré que les impacts sur les ressources sont principalement dus—quand on ne prend pas en compte les impacts liés à l'épuisement de la ressource en eau—à l'énergie de pompage (23%), la fertilisation (30%), i.e. le transport routier de la fumure (21%), la production d'ammonitrate (9%) et la fabrication des tuyaux d'irrigation. Cependant les impacts spécifiques sur l'épuisement de la ressource en eau sont écrasants quand ils sont pris en compte dans la méthode, ce qui doit absolument être fait dans ce contexte de rareté des ressources en eau et compte tenu des modélisations climatiques prévoyant une rareté accrue à l'avenir. Copyright © 2018 John Wiley & Sons, Ltd.